Effect of Head Teachers’ Managerial Styles on the Teachers’ Professional and Organizational Commitment - Muhammad Abdullah Khan, Shafqat Hussain (PJE, 2023)
This study was aimed to investigate the effect of three managerial styles i.e. autocratic, democratic, and laissez-faire of head teachers on the professional and organization commitment of teachers at elementary level. This research is descriptive and correlation in nature. A survey instrument was self-developed and validated through expert opinions and pilot study. The stratified cluster random sampling technique was used to select 540 teachers (40 %) including 274 male and 266 female from the population. The findings of the study show that most practiced managerial style was democratic and least practice was laissez-faire. The organizational and professional commitment levels of the teachers were significantly positive correlated with democratic and negative correlated with autocratic managerial style. It is recommended that head teachers may adopt democratic managerial style to enhance the professional and organizational commitment of teachers. The Punjab Education Department may arrange the training through Directorate of Staff Development for head teachers to practice democratic managerial style to increase the organizational and professional commitment of teachers. Head teachers may develop passion of duty and commitment in teachers by making educational and organizational plan with the collaboration of teachers and assigning duties according to their abilities, interests and willingness. The effect of other variables on teachers’ commitment like national educational policies, cooperation of community and parents, work environment, academic qualification, professional qualification and experience of teachers may be examine in further studies.